The Perception of the Russian Language by Philology Students:Russian Philology Students vs. Non-Russian Philology Students - Гринько, Юлия (Slavistica Vilnensis, 2017)
This article analyses the perception of the Russian language by students of the Faculty of Philology of Vilnius University. The purpose of the study is to find out what associations are linked with the Russian language by students of different specialties, classify them by semantic areas and try to interpret them according with the sociolinguistic background of Lithuania by conducting a psycholinguistic experiment. The experiment was carried out in the Autumn of 2014 with the help of students of Lithuanian, English, Polish and Russian philology. 1 333 responses were received. The greatest number of semantic areas to distinguish was derived from the students of Russian philology, who provided more associations as compared to philologists of other languages. For those informants who have a poor command of Russian or do not know the language at all the associations are more often based on political and historic events.